(untitled) (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Kristiana R, Sibero MT, Farisa MY, Ayuningrum D, Dirgantara D, Hanafi M, Radjasa OK, Sabdono A, Trianto A. 2019. Antibacterial potential of nudibranch-associated bacteria from Saparua and Nusa Laut Islands, Indonesia. Biodiversitas 20: 1811-1819. Infections caused by multidrug-resistant bacteria are the international health issue that triggers the urgency of finding new antibacterial agents. The aim of this study was to obtain the nudibranchs-associated bacteria that have bioactivity against multidrug-resistant bacteria. A total of 13 species of nudibranch were identified based on morphological characterization. Overlay methods were used for the screening of the isolates bioactivity against six pathogenic multidrug-resistant bacteria. The Minimum Inhibition Concentration (MIC) of the crude extract was evaluated against Methicillin-resistant Staphylococcus aureus (MRSA), Escherichia coli, Bacillus subtilis, Klebsiella pneumonia, Micrococcus luteus, and Extended Spectrum Beta Lactamases E. coli (ESBL) using MTT method. A total of 145 isolates were obtained which eleven of the isolates showed antibacterial activity against the pathogenic bacteria. The MIC tests showed that the best acivity was isolate SM-S-9-15 and SM-N-3-7. The methanolic extract of isolate SM-S-9-15 active to all of the pathogenic bacteria, while the ethyl acetate extract of the isolate SM-N-3-7 active to the E. coli, B. subtilis, K. pneumonia at the concentration of 500 mg/mL. According to 16S ribosomal RNA gene sequence-based identification, all active isolates belong to Virgibacillus marismortui, V. dokdonensis, Bacillus kochii, Vibrio algynoliticus, and Pseudoalteromonas piscicida.